Untersuchung und Modellierung des viskoplastischen Verformungsverhaltens oxidpartikelverstärkter Stähle - Straßberger, Luis (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2018)
The high-temperature deformation behavior of oxide dispersion strengthened steels was investigated and correlated to the resulting microstructure using electron microscopy. Viscoplastic constitutive equations were developed from the results to model the deformation behavior.